Soccer Teaching the Basics
In this section of the manual, you'll find a set of practice plans designed to help you through your first season of coaching. We want to stress that these practices are not the "be all and the end all" by any means, and that there are as many ways to teach these basic skills as there are practising coaches. These are simply intended to help you get started. As you develop as a coach, you'll find that you begin to pick up more and more ideas about how to teach and improve your players' skills, and as your players improve you'll find that they increasingly challenge you to develop your coaching skills. Here's what you'll find in this section: Ball control 1.Straight-ahead dribbling 2.Dribbling moves 3.Chops 4.Inside cut 5.Fakes & feints Passing & receiving 1.Push pass 2.Passing & receiving 3.Receiving 4.Chest traps 5.Receiving 'air balls' 6.Shielding 7.Heading intro 8.Heading Kicking 1.The instep drive 2.The laces kick 3.The lofted kick Defending 1.Tackling 2.Shoulder charge 3.Communication 4.First defender 5.Second defender 6.Basic marking Attacking 1.Taking defenders on 2.Going 1v1 3.Combined play 4.Communication Other 1.Throw-ins 2.Restarts 3.Tips on basic goal-keeper training 4.Sample stretching routine 5.Teaching the LOTG 6.Games and activities from the SOCCER-COACH-L Archives 7.On-field communication